2017
DOI: 10.1002/asi.23928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social influence of multichannel access in an online health community

Abstract: Social influence has a great impact on human behavior, which has been widely investigated in various research fields. Even so, it has rarely been investigated in the online health community. In this paper, we focus on the multichannel access in online health communities, defining social influence as the average degree of multichannel access to a physician's colleagues. Based on the multinomial logistic regression model, we examined the direct effects of social influence and patients' rating to multichannel acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…We tested the mediation effect of fear by following Luo et al (2018) in adopting the following steps, and the results are shown in Table 5 . We first checked the effects of peer communication and peer condition on rumor sharing behavior in Model 7, and the impacts were positive and significant (PO: β = 0.21, p < 0.001; PC: β = 0.42, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…We tested the mediation effect of fear by following Luo et al (2018) in adopting the following steps, and the results are shown in Table 5 . We first checked the effects of peer communication and peer condition on rumor sharing behavior in Model 7, and the impacts were positive and significant (PO: β = 0.21, p < 0.001; PC: β = 0.42, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…As a type of virtual community, online health communities (OHCs) are developed with the Web 2.0 technology [1,2]. OHCs are platforms for people to communicate with one another regarding health-related topics, thereby promoting the interaction between physicians and patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although many features may impact payment, we are particularly interested in those, which are publicly visible on the platform, such as characteristics of physicians and their interaction with patients and patient feedback, rather than nonvisible features, such as patients' economic status and their general attitude toward technology. This is because publicly visible features contain information and signals that, through observational learning and social influence [20][21][22][23], may influence patient payment.…”
Section: Gaps and Objectivesmentioning
confidence: 99%